Fungsi dan Makna Pantun Upacara Sekujang Masyarakat Serawai di Desa Tapak Gedung Kabupaten Kepahiang Provinsi Bengkulu - Saputra, Ade Bayu; Manjato, Ajat (DIKBASTRA: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to describe the function and meaning of pantun in sekujang ceremony of Serawai community in Tapak Gedung Village, Kepahiang Regency. The sekujang ceremony is held on the second or third day of Eid as a form of supplication and expression of gratitude through rhymes. This research used descriptive qualitative method with data collection techniques through semi-structured interviews, participatory observation, and documentation. Data analysis was conducted using an interactive approach consisting of data reduction, data presentation in the form of narratives and pantun quotations, and conclusion drawing through interpretation of the socio-cultural context. Data validity was strengthened through source triangulation, peer discussion, and member checking. The results showed that pantun in sekujang ceremony functions as a symbolic communication medium that conveys messages implicitly and politely, strengthens social interaction, and becomes a vehicle for preserving local cultural values. The functions of pantun include aesthetic aspects (beauty of sound and rhyme), phatic (maintaining social communication), conative (directing listener response), and emotive-referential (conveying emotions and cultural information). Apart from being entertainment, pantun also plays an educative role in teaching manners and strengthening solidarity through the egalitarian practice of meradai. The meaning of pantun reflects respect for ancestors, the value of politeness, and social solidarity that maintains harmony in the life of the Serawai people. This research recommends the preservation of pantun values to encourage the sustainability of traditions and awareness of the younger generation towards local culture.